Relationship Between Autism Spectrum Disorder and Maternal Exposure to Passive Smoking and Environmental Factors: A Case‐Control Study in Bangladesh - Md. Shahid Khan; Mohammad Alamgir Kabir; Shafi M. Tareq (Health Science Reports)
ABSTRACT Background and Aims Pre and postnatal environmental exposures can influence gene expression and significantly contribute to the development of autism spectrum disorder (ASD). Bangladesh, recognized as the world's most polluted country, faces a dearth of comprehensive studies focusing on environmental factors associated with ASD. In this observational case‐control study, an exploration was conducted into the relationships between ASD risk and exposure to maternal passive smoking and environmental factors within Bangladesh. Methods Twenty‐four out of 103 “Protibandhi Sheba O Shahajjo Kendro” (PSOSK, the disability support and service centers) were selected using a simple random sampling method, ensuring a representative distribution across each division of Bangladesh. A structured questionnaire was used about exposure to maternal passive smoking and related environmental factors. The questionnaire was filled out by face‐to‐face interviews with parents of 310 ASD individuals and 310 healthy controls from January 2020 to June 2021. IBM SPSS version 23 was used for uni‐variate, bi‐variate, and multivariate logistic regression analyses. The significance level was p ≤ 0.05, and the odds ratio (OR) was within 95% confidence intervals (CIs), to determine whether the variable is a risk. Results Exposure to maternal passive smoke, living within a mile of a highway, and using household mosquito aerosol (repellents) during pregnancy and early childhood were all significantly linked to an increased risk of ASD (n = 310 each) in this study. Conversely, maternal residence in an urban and brick kiln within one mile of their residence during pregnancy to 3 years postnatal life was significantly associated with a decrease in the adjusted odds of ASD in offspring. Conclusion Exposure to maternal passive smoke and household aerosols, along with proximity to highways within one mile during pregnancy and early childhood, increased the odds of ASD. Further research is imperative to overcome the inconsistency and to observe and generalize the association.